Changing in modern Malaysian pattern of life and its implication to the ageing community - Sarzali, Siti Aidila; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni (AENSI Publications, 2015)
Malaysia as the developing countries had made each of its city to be a magnet of working opportunity for people to move to the urban and make a living at the city. The lifestyle changes to conservative tradition to modern dynamic thinking. This phenomenon has led to the objectives of this paper writing which will focus more on the lifestyle of the Malaysia society and its implication to the ageing community. The content of these paper writing will start with an introduction, definitions of the keywords such as elderly, Malaysia society, urban and rural lifestyle, reviews on Malaysia society and the implication to the ageing community and last but not least summary for the paper writing. The methodology used in these paper writing is to compare the lifestyle in the past and modern Malaysia society and the impact to the ageing society. The aim for this writing is to make people understand and aware of the changes of the lifestyle and its impact to the ageing society.